Bacterial Endocarditis Caused by : First Reported Case and Literature Review - Chanita Phichaphop MD; Nopporn Apiwattanakul PhD, MD; Suthep Wanitkun MD; Sophida Boonsathorn MD (SAGE Publishing, 2020)
Actinomyces species are gram-positive, facultative anaerobic bacilli. Infection caused by Actinomyces species is usually limited to cervicofacial, thoracic, and abdominopelvic regions. Infective endocarditis due to Actinomyces species is extremely rare with only 30 reported cases since 1939. We report a case of Actinomyces oris endocarditis in a 14-year-old boy who had a 2-week history of dyspnea on exertion without other constitutional signs. Transthoracic echocardiography was suggestive of perforation of the right coronary cusp of aortic valve. No organisms were isolated from blood cultures. The patient underwent surgical valve repair due to deteriorated cardiac function. Valve tissue culture did not initially identify the organism. However, the terminal subculture in a thioglycolate broth grew gram-positive bacilli. The matrix-assisted laser desorption ionization time-of-flight mass spectrometry (MALDI-TOF MS) was compatible with Actinomyces oris . After 6 weeks of intravenous ampicillin, the patient remained well with improved cardiac function. We reviewed all reported cases of infective endocarditis caused by Actinomyces species, commenting on clinical characteristics and factors associated with unfavorable outcomes in infective endocarditis due to Actinomyces species. Although infective endocarditis caused by Actinomyces spp is rare, it could be considered in a case of culture-negative endocarditis since the clinical features might be indistinguishable from other bacterial endocarditis. Additionally, MALDI-TOF MS is a useful diagnostic tool for the identification of Actinomyces spp to improve the accuracy of diagnosis.